The Development of Waste Bank Management to Improve Household Income in Surakarta City - Antriyandarti, Ernoiz; Barokah, Umi; Rahayu, Wiwit; Mandasari , Putriesti (BRIN Publishing (Penerbit BRIN), 2024)
Establishing a waste bank in Surakarta City is not only intended to manage household waste The waste bank can also serve to improve the community's economy. Since 2014, the Surakarta City Environmental Services (DLH) has been promoting the formation of waste banks. There were 123 waste banks recorded in Surakarta City until 2020; in 2021, only 70 remained. Furthermore, not all waste banks can run well. Therefore, this study examines how to develop waste bank management to improve household income in Surakarta City. This study used a descriptive method and Miles and Huberman analysis using 120 waste bank customers and 13 managers as respondents. The result showed that the waste bank contribution to the household income was IDR 26,461/month, which means that some aspects need improvements, such as human capacity, infrastructure and facilities, time management, economic incentives, and the program itself. This study provides recommendations on how to maintain and increase waste bank activities to enhance household welfare and environmental quality.